Malaysian Primary Care Providers’ Views On People Who Use Drugs And Its Associated Factors - Shamsul Bahrin, Nasehah Sakeenah; Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2025)
Objectives: Drug misuse and abuse pose major public health challenges worldwide. In 2019, around 36.3 million people globally were affected by substance use disorders (SUD), with 100,000 of people actively using drugs in Malaysia. Individuals with SUD frequently disengaged out of treatment, highlighting the need for non-judgmental attitudes among healthcare providers. Islam, as the second-largest religion, accounting for over 23% of the global population, also plays a critical role in shaping perspectives on health, including substance use and recovery. This study evaluates the perception of Primary Care Providers (PCPs) toward people who use drugs (PWUD) and the associated factors. Methods: A cross-sectional study was conducted from June 2021 to November 2023 in primary care clinics in Selangor, employing nonprobability sampling. Participants completed an online self-administered questionnaire, with perceptions measured using the Drug and Drug Problems Perception Questionnaire (DDPPQ). Responses were rated on a 4-point Likert scale, where lower scores indicate more favourable perceptions. Multiple regression analysis identified factors associated with PCPs perceptions. Results: A total of 233 PCPs participated in the survey. They were mostly female (76.8%), medical officers (46.8%), with a median of 8 years of primary care experience. While a significant majority (73.4%) encountered SUD patients, less than half received addiction-related training, including the Methadone Maintenance Therapy (MMT) Programme (23.2%), detoxification programmes (7.7%), and Alcoholics or Narcotics Anonymous Programmes (14.2%). The mean + sd total DDPPQ score was 45.38±6.91, out of a total score of 80 reflecting a generally negative perception. A significantly less negative perception was associated with PCPs having MMT programme experience (p<0.001) and higher interaction frequencies with SUD patients (p<0.001). Conclusion: PCPs in this study exhibited a generally negative perception towards SUD patients. A negative perception was associated with PCPs who had no experience with MMT and a lower frequency of interaction with SUD patients. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S45